Dental management of patients with X-linked hypophosphatemia - Lee, Bin-Na; Jung, Hye-Yoon; Chang, Hoon-Sang; Hwang, Yun-Chan; Oh, Won-Mann (Restorative dentistry & endodontics, 2017)
X-linked hypophosphatemia (XLH) is a hereditary metabolic disease caused by the loss of phosphate through the renal tubules into the urine, and an associated decrease in serum calcium and potassium phosphate. Its dental features include spontaneous dental abscesses that occur in the absence of trauma or dental caries. The aim of this case report was to describe the dental problems of XLH patients and to evaluate limitations in their treatment. A 14 year old male and a 38 year old female with XLH were referred to the Department of Conservative Dentistry for endodontic treatment. The dental findings were periapical abscesses without obvious trauma or caries. Conservative endodontic treatment was performed in teeth with pulp necrosis and abscess. In case 1, the treated teeth showed improvements in bone healing, without clinical symptoms. However, in case 2, the implants and the treated tooth showed hypermobility, and the final restoration was therefore postponed. Early diagnosis, periodic examinations, and communication with the patient's pediatrician are important in the dental management of patients with XLH.